MENINGKATKAN KEMAMPUAN ADVANCED MATHEMATICAL THINKING DAN HABITS OF MIND MAHASISWA MELALUI PENDEKATAN KETERAMPILAN METAKOGNITIF - Masta Hutajulu; Eva Dwi Minarti (Department of Mathematics Education, Universitas Kuningan, 2017)
ABSTRACTThis research is conducted as a preliminary study that aims to determine the achievement and improvement of advanced mathematical thinking skills of students. In college, mathematics is generally more difficult and complex than ever. This is because the material given is more abstract. Therefore, mathematics and mathematics education students are expected to construct mathematical definitions/concepts independently, to prove logically, and to further develop their mathematical abilities. In fact, the learning process in the classroom does not improve the ability of mathematical thinking and even tends not to awaken the habits of the mind of the student, hence to overcome the problem, this research is studied a learning approach, the metacognitive skill approach. This research is an experimental research with research instrument that used is test of advanced mathematical thinking ability of student and student habits of mind scale. This research was conducted on final year students who contracted real analysis courses at STKIP Siliwangi Bandung. Based on the results of the research, it is known that the achievement and improvement of advanced mathematical thinking skills of students who gain learning with metacognitive skills approach is better than those who get regular learning. In general, students who gain learning with a metacognitive skills approach habits of mind better on ordinary learning..Keywords: Advanced Mathematical Thinking, Habits of Mind, Metacognitive Skill Approach.